2021
DOI: 10.1038/s41598-021-90616-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 4-week physical exercises on tryptophan, kynurenine and kynurenic acid content in human sweat

Abstract: The aim of the study was the detection of TRP, kynurenine (KYN), and kynurenic acid (KYNA) in human sweat, and determining whether physical activity affects their content in this secrete. Two different methods were used simultaneously—collection of sweat by means of an absorption pad from the inter scapular region, and collection of a drop of sweat from the region of the forehead. Quantitative determinations of TRP, KYN and KYNA were performed using high performance liquid chromatography with ultraviolet and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Regarding the effect of long-term exercise on KYNA, a recent study of 4-week physical exercises on human found that physical exercises promote an increase in the amount of KYNA in sweat on day 14. The KYNA level returned to baseline on day 28 ( 66 ). Additionally, inhibition of KYATs reduces myotube oxidative capacity and exercise performance in mice ( 67 ).…”
Section: Links Between Kyna and Common Metabolic Diseasesmentioning
confidence: 96%
“…Regarding the effect of long-term exercise on KYNA, a recent study of 4-week physical exercises on human found that physical exercises promote an increase in the amount of KYNA in sweat on day 14. The KYNA level returned to baseline on day 28 ( 66 ). Additionally, inhibition of KYATs reduces myotube oxidative capacity and exercise performance in mice ( 67 ).…”
Section: Links Between Kyna and Common Metabolic Diseasesmentioning
confidence: 96%
“…The reaction is catalyzed by tryptophan-2,3-dioxygenase (TDO) or indoleamine-2,3-dioxygenases 1 and 2 (IDO). TDO is a constitutive enzyme present mainly in the liver [ 66 ]. KYNA is enzymatically produced from a key intermediate compound in the tryptophan catabolic pathway, KYN [ 67 ].…”
Section: Biochemical Connectionmentioning
confidence: 99%
“…KYNA is enzymatically produced from a key intermediate compound in the tryptophan catabolic pathway, KYN [ 67 ]. KYN and its metabolites, collectively known as kynurenines, exhibit diverse biological activities [ 66 ]. Initially, both quinolinic acid and KYNA, a glutamate agonist and antagonist, respectively, were shown to be involved in the control of neurotransmission, neuronal cell membrane excitability, and neurodegeneration [ 66 , 68 ].…”
Section: Biochemical Connectionmentioning
confidence: 99%
See 2 more Smart Citations